Peningkatan Keamanan Login Pada Content Management System (CMS) Wordpress Dengan Implementasi Notifikasi Login Dengan Whatsapp Gateway - Muhammad Najamuddin Dwi Miharja; Ahmad Fauzi (Teknik Informatika, Universitas Pelita Bangsa, 2021)
According to data from internetworldstats, internet users in Indonesia are the third largest in Asia, reaching 212.35 million in March. However, with the increasing number of internet users in Indonesia, there are still many data leaks, especially in terms of website security. Wordpress is one of the most popular CMS in the world, so it is very likely that there are security vulnerabilities. In this study the author will implement a notification system using the whatsapp gateway every time there is a login to the system. The implemented system turns out to be running well and can increase security in monitoring web logins on the wordpress system. Keywords: content management system (CMS), security, notification, whtasapp gateway.